Digitization Of Arabic Lexicology In The 5.0 Era - abdulazis; Vidia Astuti, Nani (Pascasarjana Universitas Islam Negeri Mataram, 2024)
This research aims to analyze and determine 1) the role of digital technology in lexicology research, 2) ⁠⁠ a ​​digital lexicography system for Arabic, and 3) the benefits and challenges of digitizing Arabic lexicology. The research method that researchers use is qualitative research with a library study type of research. The results of this research are: 1) Digital technology has had a significant impact on lexicology research, increasing efficiency, accessibility, and collaboration. With advanced tools and techniques like N.L.P., machine learning, and cloud storage, lexicology researchers can collect, analyze, and disseminate data more effectively and innovatively, enriching researchers' understanding of the language. 2) The digital lexicography system for Arabic consists of various technological components that combine to provide comprehensive and easily accessible linguistic information, such as utilizing digital corpora, lexical databases, N.L.P. tools, intuitive user interfaces, mobile applications, and data visualization tools. 3) Digitization of Arabic lexicology offers excellent benefits in terms of accessibility, research efficiency, data updates, collaboration, and visualization. However, challenges such as dialect diversity, data quality, technology infrastructure, data security, language complexity, and technology education need to be addressed to maximize the potential of this digitalization.